Figurative Language Used In Owl City's Albums: A Pragmatics Perspective - Yulidar, Luthfi; , Nur Hidayat, M.Pd; , Siti Zurhriah Ariatmi, M. Hum (2014)
The study belongs to descriptive qualitative research. The research aims to identify the types of figurative language and illocutionary act in the lyric of Owl City's Albums. This research uses pragmatics approach to find out the illocutionary act. The objects of the research are lyrics in the Owl City's album entitled Ocean Eyes and Maybe I'm Dreaming which consist of 19 songs. In collecting data, writer uses the document. The data in this research are figurative language, they are metaphor, simile, personification, symbol, paradox, and hyperbole. The illocutionary meanings are thanking, asserting, stating, suggesting, boasting, complaining, ordering, requesting, advising, recommending, blaming, praising, and condoling. From the collected data, the writer finds 50 data. Based on the research finding, the writer found that figurative language of hyperbole is the most appeared in the lyric of Owl City's albums. Then, Personification, Simile, Metaphor, Symbol and the last is Paradox. The figurative language of hyperbole is most appearing in the Owl City's song because the characteristic of the song-writer uses excessive words to express his feel to be a song. The next research finding is the illocution of the figurative language. Here, there are 13 illocution of Figurative Language used in Owl City's albums. There are thanking, asserting, stating, suggesting, boasting, complaining, ordering, requesting, advising, recommending, blaming, praising, and condoling. Based on the analysis, the results of the kinds of speech act is that there is asserting. It is the most commonly found in the analysis. The next illocution act that found is stating, requesting, complaining, thanking, advising, praising, and blaming. The last are boasting ordering, recommending, and condoling.